2022
DOI: 10.3390/plants11131744
|View full text |Cite
|
Sign up to set email alerts
|

Species-Level Differences in Osmoprotectants and Antioxidants Contribute to Stress Tolerance of Quercus robur L., and Q. cerris L. Seedlings under Water Deficit and High Temperatures

Abstract: The general aim of this work was to compare the leaf-level responses of different protective components to water deficit and high temperatures in Quercus cerris L. and Quercus robur L. Several biochemical components of the osmotic adjustment and antioxidant system were investigated together with changes in hormones. Q. cerris and Q. robur seedlings responded to water deficit and high temperatures by: (1) activating a different pattern of osmoregulation and antioxidant mechanisms depending on the species and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 116 publications
4
16
0
Order By: Relevance
“…A large body of literature has been devoted to explaining how the increased stress resistance to heat in plants is related to the increased content of different osmolytes such as proline or glycine betaine, which is why many genetically engineered plant strategies are directed toward the production of plants that overproduce GB and proline and express increased tolerance to abiotic stresses (drought, salt, cold, or high-temperature stresses) [ 63 , 64 , 65 , 66 ]. In our study, non-mycorrhized oak seedlings increased proline levels (a 1.46-fold increase) after heat stress exposure compared to non-treated controls, which is consistent with previously reported data for pedunculate oaks [ 16 , 67 ]. Proline is an important marker of abiotic stress, including high temperature, because it is an important antioxidant and ROS quencher that is associated with the regulation of redox balance, osmotic pressure, energy status, nutrient availability, photosynthesis, and mitochondrial respiration, while also acting as a signaling molecule that modulates gene expression [ 46 , 68 , 69 , 70 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A large body of literature has been devoted to explaining how the increased stress resistance to heat in plants is related to the increased content of different osmolytes such as proline or glycine betaine, which is why many genetically engineered plant strategies are directed toward the production of plants that overproduce GB and proline and express increased tolerance to abiotic stresses (drought, salt, cold, or high-temperature stresses) [ 63 , 64 , 65 , 66 ]. In our study, non-mycorrhized oak seedlings increased proline levels (a 1.46-fold increase) after heat stress exposure compared to non-treated controls, which is consistent with previously reported data for pedunculate oaks [ 16 , 67 ]. Proline is an important marker of abiotic stress, including high temperature, because it is an important antioxidant and ROS quencher that is associated with the regulation of redox balance, osmotic pressure, energy status, nutrient availability, photosynthesis, and mitochondrial respiration, while also acting as a signaling molecule that modulates gene expression [ 46 , 68 , 69 , 70 ].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, we reported the species specificity of pedunculate oaks toward increased temperature stress, and we proved that thermotolerance in pedunculate oaks has been mostly conferred by increased osmolyte levels (glycine betaine, GB and dimethylsulfoniopropionate, DMSP) [ 16 ], but the effect of ectomycorrhizal fungi in the mitigation of high-temperature stress in pedunculate oaks has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Mahan had the lowest N a and medium P max and YLC35 had higher N m and the highest P max , yet they all presented the highest PNUE ( Figure 2 ), echoing that adaptable varieties tend to have lower LMA, higher P max , and PNUE in order to grow faster and yield more [ 32 , 33 ]. Kebert et al [ 4 ] also suggested that plant thermotolerance could be revealed by the maintenance of photosynthetic functionality. This may demonstrate that Mahan and YLC35 triggered a shift of plant traits along the leaf economic spectrum towards faster growth strategies involving higher photosynthetic capacity and N utilization, while YLC29, YLJ042, and YLJ5 had lower tolerance even though more N was absorbed.…”
Section: Discussionmentioning
confidence: 99%
“…Our result showed that YLJ5 had the highest PRO yet had the lowest SPC and SSC, and YLJ042 had lower PRO while having the highest SPC and SSC ( Figure 4 a–c). This implied that plant tolerance to high temperatures may rely on compensation mechanisms [ 4 ]; that is, the eight varieties selectively increased the levels of adjustors in the same protective systems for reducing membrane damage depending on their varietal characteristics. Therefore, the level of MDA, together with different osmotic parameters at high temperatures, suggested an adaptation to stress for the test varieties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation